المكتبات المدرسية بالمؤسسات التربوية الجزائرية بين الواقع والطموح- دراسة ميدانية ببعض متوسطات وثانويات مدينة الوادي - - بنين, إبتسام; بنين, آمال; علاق, مباركة (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة إلى تشخيص واقع المكتبات المدرسية بالمؤسسات التربوية الجزائرية من خلال دراسة ميدانية شملت عينة من مؤسسات التعليم المتوسط والثانوي بمدينة الوادي. وباتباع المنهج الوصفي الاستكشافي واستخدام التكرارات والنسب المئوية كأسلوبين احصائيين توصلت الدراسة إلى عدة نتائج تشير في مجملها إلى وجود المكتبة المدرسية كهيكل مادي يشمل إلى جانب القاعة المخصصة للمكتبة رصيدا وثائقيا يضم مئات العناوين وآلاف الكتب التي لا تجد طريقها إلى جمهور القراء معلمين ومتعلمين نظرا لعدة عوامل أبرزها النقص الفادح في التأطير وقلة الاعتمادات المالية وغياب المبادرات الحقيقية لتفعيل خدمات المكتبة المدرسية في الوسط التربوي.The study aimed to diagnose the reality of school libraries in Algerian educational institutions through a field study that included a sample of middle and secondary education institutions in El- Oued. By using the descriptive exploratory approach , iterations and percentages as two statistical methods, the study reached several results that indicate in its entirety the existence of the school library as a physical structure that includes alongside the hall designated for the library a documentary balance that includes hundreds of titles and thousands of books that do not find their way to the readership of teachers and learners due to several factors most notably The severe shortage of supervision , the lack of funds and the absence of real initiatives to activate the services of the school library in the educational community.
School libraries in Algerian educational institutions between reality and ambition a field study of middle and secondary education institutions in El- Oued.
مقال
Keywords: المطالعة، المكتبات المدرسية ، المؤسسات التربوية.; reading , school libraries , educational institutions.